Mulheres pescadoras: um estudo antropológico sobre saberes, práticas e vivência no espaço pesqueiro em Porto dos Milagres, Santarém - Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
This work directed interest in reflections and analyzes on the fisherwomen in Porto dos Milagres, located in the neighborhood of Uruará, in the city of Santarém, Pará. It is observed the participation of women fishers as a political, economic and social subject. An anthropological study aimed at knowledge, practices, gender, empowerment and visibility before the fishing community. Starting from the field work on ethnographic data, the different forms of action of the fisherwomen working in the meetings, the fishing activity and the domestic environment are observed. It was used as a method of data collection, questionnaires and semistructured interviews with 9 women fishers through direct observation and informal conversations. Through this monograph, it is possible to demonstrate that Fishers act politically, economically and socially in the context of fishing. And value their social category.
Keywords: Empoderamento Feminino; Mulheres pescadoras; Porto dos Milagres; CNPQ:: CIÊNCIAS HUMANAS